Dissolution kinetics of copper in lead-free liquid solders. Issue 2 (7th April 2015) - Faizan, Mohammad
Abstract : Purpose: – The purpose of this paper was to develop a physics-based mathematical model to estimate the amount of substrate metal lost during the wet soldering process. Design/methodology/approach: – A mathematically rigorous model depicting the actual physics of the substrate/solder interaction and dissolution has been proposed to simulate the dissolution of the substrate metal in the liquid lead-free solder. The basic mass diffusion equation with the implementation of interface reaction kinetics was solved numerically using the finite volume approach. The moving interface was tracked by utilizing the coordinate transformation technique. Findings: – It was observed that the process of metal dissolution in the liquid solder was governed by two important parameters, viz., interface kinetics and long-range diffusion in the liquid solder. Non-equilibrium behavior was observed in the early stage of the process. The early stage of the dissolution process was seen as governed by interface kinetics, while diffusion became the rate-controlling mechanism at the later phase of soldering. Practical implications: – Substrate dissolution can be accurately estimated for a particular substrate–solder combination and for the given process conditions. This early estimation will help in ensuring the reliability and health of the solder joint. Originality/value: – A model based on actual physics is proposed, and interface reaction kinetics has been introduced to capture the actual behavior of the process. The model will serve as the basis for two- and three-dimensional analysis, including the formation of an intermetallic compound in the solder joint.